Evaluation of Selected Pharmacological Properties of a Polyherbal Extract (Aju Mbaise) in Experimental Rats - Robert Ikechukwu Uroko; Nnah Solomon Ijioma; Henry Nnaemeka Ogbonna; Nancy Oluomachi Uchenna (Biology, Medicine, & Natural Product Chemistry, 2025)
Aju Mbaise, an herbal combination widely utilized in southeastern Nigeria for managing postpartum complications and alleviating menstrual pain, was evaluated for analgesic, anti-inflammatory, and anti-diarrheal properties in rats. Specific objectives included evaluating anti-diarrheal effects, examining anti-inflammatory effects and assessing analgesic properties of the herbal combination. The study involved subjecting the Aju Mbaise polyherbal extract (APE) to phytochemical analysis and acute toxicity testing. Anti-diarrheal effects were evaluated by administering charcoal as a meal and using castor oil-induced models. Anti-inflammatory effects were assessed through the carrageenan-induced paw oedema model, and analgesic properties were examined using the acetic acid-induced pain model. Phytochemical analysis identified alkaloids, tannins, phenols, steroids, cardiac glycosides, terpenoids, flavonoids, and saponins in the extract. The acute toxicity value exceeded 5000 mg/kg body weight, indicating safety. In animal studies, APE exhibited significant inhibitory effects on intestinal motility, reduced wet stool frequency, and influenced the castor oil-induced diarrhoea and enhanced anti-inflammatory activities. Additionally, it demonstrated a reduction in acetic acid-induced pain in rats. The APE with its diverse phytochemical composition, possesses anti-diarrheal, anti-inflammatory, and analgesic properties. However, further research is needed to establish ideal dosages and potential adverse effects.